2017
DOI: 10.18632/oncotarget.16538
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of long non-coding RNA TINCR contribute to the susceptibility and progression of colorectal cancer

Abstract: Colorectal cancer (CRC) accounts for the leading causes of cancer-related morbidity and mortality. However, a large part of heritable factors are warranted to be explored. Long non-coding RNAs (lncRNAs) serve critical roles in cancer development and progression. Herein, we explored effect of genetic variants of Tissue differentiation-inducing non-protein coding RNA (TINCR), a key lncRNA required for somatic tissue differentiation and tumor progression, on risk and progression of CRC. Three tagSNPs, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
(36 reference statements)
0
28
0
Order By: Relevance
“…Since their discoveries, a large amount of lncRNA has been found being dysregulated in a range of cancers [5]. In addition, they are being identified and characterized for serial steps of cancer development, including tumor initiation, growth, and metastasis [6]. Maternally expressed gene 3 (MEG3), a lncRNA that has attracted much research interest, is aberrantly expressed in several human cancers including ovarian cancer [7], gastric cancer [8], colorectal cancer [9], cervical cancer [10], and malignant glioma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since their discoveries, a large amount of lncRNA has been found being dysregulated in a range of cancers [5]. In addition, they are being identified and characterized for serial steps of cancer development, including tumor initiation, growth, and metastasis [6]. Maternally expressed gene 3 (MEG3), a lncRNA that has attracted much research interest, is aberrantly expressed in several human cancers including ovarian cancer [7], gastric cancer [8], colorectal cancer [9], cervical cancer [10], and malignant glioma [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ma et al found that SNPs of the lncRNA TINCR were significantly associated with decreased gastric cancer susceptibility by decreasing its gene expression levels. Moreover, a study by Zheng et al found that lncRNA TINCR polymorphisms were associated with the progression of colorectal cancer, and SNP rs2288947 may be a biomarker with the occurrence and progression of colorectal cancer. In our case‐control study with 248 patients with recurrent miscarriage and 392 healthy controls from the Southern Chinese population, we did not observe a significant relationship between the TINCR gene rs2288947 A > G polymorphism and the recurrent abortion susceptibility of women in Southern China.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Recently, studies have found that genetic variation in TINCR was associated with a variety of diseases, such as the SNP rs2288947, which contributed to the susceptibility and progression of colorectal cancer and susceptibility to gastric cancer. 19,20 Furthermore, studies have found that some genes that regulate cell proliferation, invasion, and migration are associated with susceptibility to miscarriage; for example, H19 and p53 gene polymorphisms. 8,21 These studies suggest that TINCR gene polymorphisms may be associated with recurrent miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are the largest subclass of noncoding transcripts in humans and extensively participate in cellular processes to regulate gene expression on the transcriptional, epigenetic, and posttranscriptional levels (Hung & Chang, 2010;Mercer & Mattick, 2013;Yoon, Abdelmohsen, & Gorospe, 2013). SNPs in exons of lncRNAs may change the structure of their host gene and affect both gene expression and function (Chang et al, 2013); moreover, such SNPs are involved in various types of human diseases (Du et al, 2015;Wu et al, 2013;Zheng et al, 2016Zheng et al, , 2017. For instance, exonic SNPs in LINC00673 and LINC-TINCR were associated with the development of pancreatic (Zheng et al, 2016) and colorectal (Zheng et al, 2017) cancer, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in exons of lncRNAs may change the structure of their host gene and affect both gene expression and function (Chang et al, 2013); moreover, such SNPs are involved in various types of human diseases (Du et al, 2015;Wu et al, 2013;Zheng et al, 2016Zheng et al, , 2017. For instance, exonic SNPs in LINC00673 and LINC-TINCR were associated with the development of pancreatic (Zheng et al, 2016) and colorectal (Zheng et al, 2017) cancer, respectively. However, the roles of exonic SNPs in the development of NSCL/P have not been investigated.…”
Section: Introductionmentioning
confidence: 99%